PENGGUNAAN MEDIA POHON HURUF UNTUK MENSTIMULASI KEMAMPUAN MENGENAL HURUF ANAK KELOMPOK B DI TKKN ST. MARIA TARAWALI - Prodensiana Eno; Maria Beatrix Ndai; Maria Jenia Nena; Marsianus Meka (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research aims to determine the increase in the ability to recognize letters in group B children at TKKN St. Maria Tarawali through the use of letter tree media. The type of research used was Classroom Action Research with the research subjects being Kindergarten B children with a total of 18 children. This research was carried out in two cycles, cycle one held 1 meeting and cycle two held 1 meeting. Based on cycle 1 calculations, the researchers took action with quite good results because in the BSH (developing according to expectations) and BSB (very well developed) categories, there was progress with an increase in the number of 6 children and a percentage gain of 33.3%. This shows that in the Cycle 1 actions there was a significant change. Based on table 3. above, the researcher obtained satisfactory results with a significant increase because in the BB category (not yet developed) the score was only 0, meaning that the researcher had succeeded in making improvements in cycle 2, because there were no more children who had difficulty recognizing letters. Then in terms of improvement, we have seen the BSH category (developing according to expectations), namely an increase in the average score of 84 with a percentage of 33.3%. In the BSB category (very well developed) it has obtained a score of 9 with a percentage of 50%. In this statement it can be said that there is good progress with the ease that children have received in recognizing letters with evidence that there are some children who are able to carry out activities and get 4 stars or BSB (very well developed). The results of this research show that from this two cycle research it can be concluded that using letter tree media can stimulate and improve the ability to recognize letters in children aged 4-5 years at TKKN St. Maria Tarawali.